Book Review: Joep Leerssen & Eric Storm (eds.), World Fairs and the Global Moulding of National Identities. International Exhibitions as Cultural Platforms, 1851–1958 - Johannes Koll (Studies on National Movements, 2022)
Book Review of Joep Leerssen & Eric Storm (eds.), World Fairs and the Global Moulding of National Identities. International Exhibitions as Cultural Platforms, 1851–1958